Endless highway - Carradine, David 1936-2009 (Journey Ed., 1995)
Carradine, the son of a Shakespearean actor, traces his life from a disrupted childhood, through the Beat generation and the sixties to the television show "Kung Fu".
Keywords: Carradine, David; Carradine, David -- 1936-2009; Actors -- United States -- Biography; Autobiografie; USA; Biografie